2020
DOI: 10.1016/j.mehy.2020.110005
|View full text |Cite
|
Sign up to set email alerts
|

Pirfenidone: A novel hypothetical treatment for COVID-19

Abstract: Cytokine storm, multiorgan failure, and particularly acute respiratory distress syndrome (ARDS) is the leading cause of mortality and morbidity in patients with COVID-19. A fulminant ARDS kills the majority of COVID-19 victims. Pirfenidone (5-methyl-1-phenyl-2-[1H]-pyridone), is a novel anti-fibrotic agent with trivial adverse effects. Pirfenidone is approved for the treatment of Idiopathic Pulmonary Fibrosis (IPF) for patients with mild to moderate disease. Pirfenidone could inhibit apoptosis, downregulate AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 61 publications
2
68
0
2
Order By: Relevance
“…This has led to several proposals for consideration of antifibrotic therapies to prevent or to treat COVID -19 pneumonia. (19)(20)(21) One CT study showed imaging features of interstitial fibrosis such as interstitial thickening, air bronchograms, irregular interface, coarse reticular pattern and parenchymal bands in 44% of patients discharged after treatment for COVID-19. (17) The aim of this report is to document the evolution of DAD to the fibrosing pattern in a series of minimally invasive autopsies in thirty individuals who died from COVID-19 in Wuhan, China.…”
Section: Introductionmentioning
confidence: 99%
“…This has led to several proposals for consideration of antifibrotic therapies to prevent or to treat COVID -19 pneumonia. (19)(20)(21) One CT study showed imaging features of interstitial fibrosis such as interstitial thickening, air bronchograms, irregular interface, coarse reticular pattern and parenchymal bands in 44% of patients discharged after treatment for COVID-19. (17) The aim of this report is to document the evolution of DAD to the fibrosing pattern in a series of minimally invasive autopsies in thirty individuals who died from COVID-19 in Wuhan, China.…”
Section: Introductionmentioning
confidence: 99%
“…A recent hypothesis has suggested that pirfenidone might be a potent therapeutic for the treatments of coronavirus disease because it could down-regulate ACE receptors expression, reduction of inflammation and improve oxidative stress, protect pneumocytes, and other cells from COVID-19 invasion. Although it has not yet been tried for the treatment of corona virusinfected patients [150]. Another research-based on epidemiological results and scientific literature suggested that pirfenidone could be used as monotherapy or along with other anti-inflammatory drugs to treat COVID-19 patients to avoid serious complications during viral infection [151].…”
Section: Pirfenidonementioning
confidence: 99%
“…To date, there are antifibrotic drugs such as pirfenidone and nintedanib used with proven efficacy in the treatment of IPF. Specifically, pirfenidone is attributed to pleiotropic actions [15] (Fig. 1).…”
Section: Pharmacological Approach With Antifibrotic Therapymentioning
confidence: 99%